Talent management in volatility, uncertainty, complexity, and ambiguity (VUCA) health environment, nurses’ psychological contract fulfillment, cordial relation and generation: moderation-mediation model - Nancy Sabry Ellethiey; Heba Mohamed Al-Anwer Ali Ashour; Nadia Hassan Ali Awad (BMC Nursing)
Abstract Background The VUCA in the healthcare environment requires combating volatility, uncertainty, complexity, and ambiguity through highly talented employees and implementing a talent management strategy. This encompasses a range of operations designed to find, attract, nurture, and utilize competent workers that impact how well nurses fulfill their psychological contracts. However, as the researchers had anticipated, several factors, such as cordial relationships and generation differences, may mediate or influence this correlation. Methods For a cross-sectional study, a non-probability convenience sampling technique was used to include n = 375 nurses from among the 600 total nurses at three private hospitals in Alexandria, Egypt. Three validated measures were used to measure the study variables and develop a mediation-moderation structural equation model. Results The result of this study revealed that nurses perceived a moderate level of talent management with a mean score of (48.91 ± 18.15), a low mean score (8.89 ± 3.93) of psychological contract fulfillment, and a moderate mean score (185.11 ± 27.02) of cordial relation. Additionally, more than half of the participants were in the Gen Z. Also, this study concluded that there is a positive mediation role of cordial relation and a negative moderation role of Gen between talent management and psychological contract fulfillment. Conclusions Using Gen as a moderating variable and cordial relations as a mediating factor, a moderating mediating structural equation model is created and validates the important influence of talent management on nurses’ psychological fulfillment, confirming the mediating effect of cordial relations and the moderating effect of genes in this relationship. GEN negatively predicted psychological contract fulfillment, meaning baby boomers predicted more psychological contract fulfillment than Z gen. Furthermore, talent management could positively predict cordial relations and psychological contract fulfillment, and cordial relations partially mediated the relationship between talent management and psychological contract fulfillment. Nurse mangers should be aware of and implement effective and talent management strategies with respecting gen difference, and apply tailored strategies for fostering nurses’ cordial relation and psychological contract fulfillment to deal with the VUCA challenging healthcare environment.